Minimizing marriage marriage, morality, and the law - Brake, Elizabeth (Oxford : Oxford University Press, 2012)
This text addresses fundamental questions about marriage in moral and political philosophy. It examines promise, commitment care, and contract to argue that marriage is not morally transformative.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Marriage -- Philosophy; Marriage -- Moral and ethical aspects; Marriage law